2015
DOI: 10.5056/jnm15019
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing Factor Changes the Phenotype and Function of Dendritic Cells in Mouse Mesenteric Lymph Nodes

Abstract: Background/AimsDendritic cells (DCs) are a significant contributor to the pathology of numerous chronic inflammatory autoimmune disorders; however, the effects of Corticotropin-releasing factor (CRF) on intestinal DCs are poorly understood. In this study, we investigated the role of CRF in alterations of intestinal dendritic cell phenotype and function. MethodsMouse mesenteric lymph node dendritic cells (MLNDCs) were obtained using magnetic bead sorting. Surface expression of CRF receptor type 1 (CRF-R1) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…CRH-induced glucocorticoids mitigate the stress response by suppressing the endocrine activity of the hypothalamus and the pituitary gland [4]. Given the ability of glucocorticoids to suppress inflammation and immune responses, the CRH family peptides additionally regulate the inflammation and immune responses at peripheral organs [5,6]. The CRH family peptides include CRH [7], urocortin I (UCN I) [8], UCN II (stresscopin-related peptide) [9], and UCN III (stresscopin) [10].…”
Section: Introductionmentioning
confidence: 99%
“…CRH-induced glucocorticoids mitigate the stress response by suppressing the endocrine activity of the hypothalamus and the pituitary gland [4]. Given the ability of glucocorticoids to suppress inflammation and immune responses, the CRH family peptides additionally regulate the inflammation and immune responses at peripheral organs [5,6]. The CRH family peptides include CRH [7], urocortin I (UCN I) [8], UCN II (stresscopin-related peptide) [9], and UCN III (stresscopin) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral CRH targets intestinal lamina propria dendritic cells whichexpress both CRH receptors [17,113,134]. Intestinal dendritic cells, as components of the adaptive immunity, internalize luminal antigens, through endocytosis, and present them to naïve T cells located in mesenteric lymph nodes [17].…”
Section: Peripheral Crh-driven Mediators Of Intestinal Inflammationmentioning
confidence: 99%
“…Previous studies have reported implication of the intestinal dendritic cells in the pathogenesis of IBD, based on their CRH-producing and secreting abilities upon bacterial stimulation [135,136]. CRH enhances inflammation in LPS-treated immortal JAWS II cells, a known DC cell line derived from BMDCs of a C57BL/6 p53-knockout mouse, and murine mesenteric lymph node-derived dendritic cells, via distinct CRHR1-dependent mechanisms, that include stimulation of T-cell proliferation, elevation of IL-6 and MIP-1α secretion and reduction in the anti-inflammatory IL-4 levels [17,113,134]. In addition, treatment of human monocyte-derived dendritic cells with CRH attenuated IL-18 production which has an anti-inflammatory action [137].…”
Section: Peripheral Crh-driven Mediators Of Intestinal Inflammationmentioning
confidence: 99%
“…Commensal bacterial strains can stimulate the production of CRF in dendritic cell, showing that CRF derived from dendritic cell may be involved in the pathogenesis of IBS ( 36 , 37 ). JAWSII cells and mouse mesenteric lymph node-dendritic cells expressed CRFR1 and CRFR2 receptors ( 30 , 38 ). CRF promotes inflammation in mature JAWSII by increasing the production of proinflammatory IL-6 and MIP-1α and decreasing anti-inflammatory IL-4 ( 30 ).…”
Section: Involvement Of Crf Signaling In Immune Cells In Ibsmentioning
confidence: 99%
“…CRF promotes inflammation in mature JAWSII by increasing the production of proinflammatory IL-6 and MIP-1α and decreasing anti-inflammatory IL-4 ( 30 ). CRF increases the capacity of mouse mesenteric lymph node-dendritic cells to stimulate T-cell proliferation, and treatment of mesenteric lymph node-dendritic cells with CRFR1 antagonist yielded a reduced capacity to stimulate T cells ( 38 ).…”
Section: Involvement Of Crf Signaling In Immune Cells In Ibsmentioning
confidence: 99%